2022-RA-1255-ESGO Clinicopatological features and treatment outcomes of ovarian clear cell carcinoma: the pan-birmingham gynaecological cancer centre experience. (20th October 2022) - Tranoulis, Anastasios; Buruiana, Felicia Elena; Audrey Kwong, Fong Lien; Balega, Janos; Singh, Kavita
Abstract : Introduction/Background: To evaluate clinico-pathological factors and oncological outcomes in ovarian clear cell carcinoma (OCCC) Methodology: Retrospective cohort study, spanning the period 2000–2022. One-hundred women with OCCC were enrolled. Clinico-pathological, and treatment data were analysed to identify plausible predictors. Survival analysis was performed via the Kaplan-Meier method, log-rank test and Cox-regression. The census day was 1st April 2022. Results: The median age at diagnosis was 59.6 years. The majority of women were diagnosed with stage I 55/100 (55%). Of these, 28/55 (50.9%) were stage IA, 16/55 (20.1%) stage IC on the basis of rupture-only, and 11/55 (20%) stage IC on the basis of surface involvement and/or positive cytology. 45/100 (45%) of women were stage III-IV. 51/100 (51%) of women had concomitant diagnosis of endometriosis. The median PFS and OS in women with stage I was 58.00 (95% CI 29.00 – 68.00) and 189.00 (95% CI 60.00 – 189.00) months, respectively. There was statistical difference in PFS/OS in women with stage IA and IC. In the subgroup analyses, women with stage IC on the basis of surface involvement and/or positive cytology demonstrated a statistically significant decrement in both PFS (HR=3.79, 95% CI 1.12 – 22.6) and OS (HR=5.32, 95% CI 1.25–26.2). The median PFS and OS in women with stage III-IV was 24.00 (95% CI 14.00 – 47.00) and 44.00 (95% CI 19.00 – 65.00) months, respectively. The presence of residual disease was found to be a prognosticator for survival, whilst adjuvant chemotherapy or presence of endometriosis were not significantly associated with poorer outcomes. Conclusion: OCCC usually presents in young women and at early-stage. Stage IA has an excellent prognosis compared to stage IC and III/IV. Surface involvement and/or positive cytology are seemingly independent prognosticators vis-à-vis endometriosis or adjuvant chemotherapy. Owing to high chemoresistance novel treatment paradigms are warranted.